Board Characteristics, Financial Slack and R&D Investments: An Empirical Analysis of the Indian Pharmaceutical Industry. Issue 1 (2nd January 2016) - Ashwin, A. S.; Krishnan, Rishikesha T.; George, Rejie
Abstract: In this study, we examine how board characteristics, such as the independent director ratio, board size, and the number of interlocks, influence the investment of slack resources into research and development (R&D) by a firm. Both the agency theory and resource dependence theory predict a positive influence of independent director ratio on the financial slack-R&D investment relationship. However in the case of board size and number of interlocks, resource dependence theory argues for a positive moderating effect, while agency theory predicts a negative effect. The hypotheses are tested on the seven-year panel data of 172 firms in the Indian pharmaceutical industry, an emerging economy, high technology industry. We find broad support for the resource provisioning role of the board of directors, which is attributed to the emerging economy context of the Indian pharmaceutical industry, where firms face high levels of opportunity but lack resources to make use of them effectively.